Purpose and practice - Sonja Verwey; René Benecke; Clarissa Muir (Communicare)
Business thinking, engagement with stakeholders, and the practice of public relations have all been confronted with major paradigmatic shifts – especially as these are contextualized by environments that are increasingly pluralistic. This has contributed to an important question into what the education of future public relations practitioners (PRPs) should be so that they can purposefully and successfully navigate and negotiate the challenges of decision-making – that are ethical and moral in nature – in the context of complex, and diverse practice. In light of this, public relations curriculum developers and educators are challenged to address issues of purpose, values-based practice and education in order to prepare future PRPs for the ethical and moral challenges that they will encounter. In the South African context this is further complicated by the recent calls for decolonisation of South African public relations curricula. This conceptual and exploratory paper addresses the issue of practice in an age of purpose, the changing roles of public relations practitioners, and the contribution values-based education can make in addressing demands for revised, and decolonised PR curricula.